Perbandingan Budaya Politik Negara Indonesia Jepang Dalam Membangun Nilai-Nilai Anti Korupsi - Nissa Nurimani; Putri Wahyuningsih; Dinda Yusti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Political culture can also represent value systems and people who are enlightened enough to take part in collective decision-making and the formulation of public policies for everyone, and can also reflect patterns of circumstances in the life of a country. Comparing Indonesian and Japanese political cultures reveals that each has a distinct culture and political identity that is unique to the nation. Every nation seeks to transition to democratic politics by adopting a political culture that is rooted in the people, which enables these nations to achieve their goal of serving the country. Corruption and democracy are two things that can fall apart like a double-edged knife and are one of the consequences of a country determining a democratic system. This research collects data using literature study and qualitative methodology. Because Japanese society instills a Culture of Shame from an early age, it can be said that efforts have been made to eradicate corruption in the country using Law Enforcement & Prevention Efforts through these means. Malay teachings, which are a reflection of morality, are a summary of Malay culture for the Indonesian people and represent their shame.